Advances in Eye Surgery - Pacheco, Patricio A. (IntechOpen, 2016)
This is a comprehensive, practical guidebook that provides a clear overview and update of current modern techniques of ocular surgery. The chapters will be of interest to a wide audience. The chapters are written by experts with special interest and extensive clinical experience in the topics.